INFLUÊNCIA DE ESPÉCIES DE ADUBAÇÃO VERDE SOBRE A MACROFAUNA EPIEDÁFICA - SOUZA, Elen Regina Cáceres; TEZOLIN, Thiara de Azevedo; TORRES, Francisco Eduardo; ABOT, Alfredo Raul; JUNQUEIRA, Patrícia Helena (ANAIS DO ENIC, 2018)
-